Structure–charge transfer property relationship in self-assembled discotic liquid-crystalline donor–acceptor dyad and triad thin films. Issue 63 (15th June 2016) - Lee, Kwang Jin; Woo, Jae Heun; Xiao, Yiming; Kim, Eunsun; Mazur, Leszek Mateusz; Kreher, David; Attias, André-Jean; Matczyszyn, Katarzyna; Samoc, Marek; Heinrich, Benoît; Méry, Stéphane; Fages, Frédéric; et al.
Abstract : Dynamics of the photo-induced charge transfer are correlated with the structural properties of self-assembled discotic donor–acceptor dyad and triad films. Abstract : The photophysical properties of donor–acceptor (D–A) and donor–acceptor–donor (D–A–D) liquid crystalline dyads and triads based on two different discotic mesogens are examined in thin films by steady-state optical spectroscopy and subpicosecond transient absorption measurements. In these systems, triphenylene and perylene bisimide units are covalently linked by flexible decyloxy chain(s) and act as an electron donor (D) and acceptor (A), respectively. These discotic liquid-crystalline systems form well-separated D and A π-stacked columnar structures in thin films. The absorption spectra of the films indicate an aggregation of the perylene bisimide and triphenylene moieties along the columns. Steady-state photoluminescence measurements show a strong fluorescence quenching that is mainly attributed to a photo-induced charge transfer process taking place between the triphenylene and perylene bisimide units. Subpicosecond transient absorption measurements show that the photoinduced charge transfer (CT) states in the dyad and triad films are formed within 0.3 ps and recombine on a 150–360 ps time scale. In addition, a correlation between the dynamics of the charge recombination process and the spacing distances between D and A units can be established in the dyad and triad films. This study provides important information on the relationship between molecular packing and the charge transfer properties in such self-organized D and A columnar nanostructures.